First people and muskox hunting in northernmost Greenland. (2nd January 2022) - Jensen, Jens Fog; Gotfredsen, Anne Birgitte
ABSTRACT: Peary Land, and in particular the area of Jørgen Brønlund Fjord and Wandel Dal, is the only place in Greenland where prehistoric muskox hunting sites are plentiful and investigated, and it gives a unique insight into prehistoric muskox hunting. In the mid-1900s, Eigil Knuth discovered the 4400 years old muskox hunting sites, which he believed corroborated the idea of a so-called Muskox Way that formed an important part of H. P. Steensby's theorizing about the origin of the peoples of the Eastern Arctic. We revisit Steensby's theory of the Muskox Way and discuss its previous use as a culture-historical idea. We also revisit the site of Pearylandville – the largest of the Independence I (2400–2000 BC) sites in Peary Land – where muskox constituted the primary game animal for prehistoric hunters. We present and analyze the archaeological lithic and faunal material in relation to individual dwellings and suggest an intensive but very short-term occupation of Independence I in Peary Land. This analysis shows that warm season indicators in the fauna material are overrepresented in dwellings with limited lithic tool inventories.